The effects of functional training on physical fitness and skill-related performance among basketball players: a systematic review - Cao, Shudian; Liu, Jia; Wang, Zhaoran; Geok, Soh Kim (Frontiers in Physiology, 2024)
Background: Evidence suggests that functional training (FT) positively impacts physical fitness and sports performance. However, a systematic review addressing the effects of FT on basketball players remains absent. This systematic review aims to explore the influence of FT on physical fitness and skill-related performance in basketball players. Methods: We searched six databases: Web of Science, Scopus, PubMed, China National Knowledge Infrastructure (CNKI), EBSCOhost, and Google Scholar. The search utilized a combination of keywords related to FT, physical fitness, and basketball. The Eligibility Criteria of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines were followed in this systematic review. Results: 11 studies were ultimately included in this review, collectively recruiting 333 basketball players. These studies demonstrated that FT significantly improved muscle strength, linear speed, cardiovascular endurance, flexibility, balance, and muscular endurance. However, the effects of FT on power, change-of-direction speed, and basketball-related performance were inconsistent. Most studies showed FT significantly improves these three variables, but a small number of studies did not find positive effects of FT using specific tests including standing long jump, Sargent jump, touch high, lane agility, lateral shuffle, dribbling line drill, and free-throw tests. Conclusion: FT is an effective training method for enhancing physical fitness including muscle strength, linear speed, cardiovascular endurance, flexibility, balance, and muscular endurance. However, the effects of FT on power, change-of-direction speed, and basketball-related performance were divergent. Some tests were not improved after FT potentially due to the short program lengths and training session durations, varied athletic levels of players examined, and different foci of the FT exercises administered. The collective evidence suggests FT programs, especially the specific exercises prescribed, should be tailored to the desired training objectives. More studies investigating the effects of FT on physical fitness and basketball-related performance with established tests are encouraged in the future to expand the current evidence base. Systematic Review Registration:https://inplasy.com/, Identifier INPLASY202360072.